(untitled) (Journal of the College of Basic Education, 2025)
This review explores the complex interplay of genetic and environmental factors contributing to its development. Genetic predisposition, particularly involving HLA genes and immune regulatory genes, plays a crucial role. Environmental factors such as smoking, iodine intake, infections, vitamin D deficiency, and exposure to radiation can significantly influence disease onset and progression. Furthermore, lifestyle factors including pregnancy, gluten intake, and gut microbiota dysbiosis have been implicated in the development or exacerbation of HT. This review highlights the importance of considering both genetic and environmental factors in understanding the pathogenesis of HT and developing effective prevention and treatment strategies.